Development of a Performance Based Teacher Education Curriculum. Final Report - Clark, Paul A.; Milligan Coll., TN. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
GRADES OR AGES: College. SUBJECT MATTER: Developmental psychology, the teaching of reading, teacher education, science for the grades, physical education, health education, teaching a directed reading lesson, music in the elementary school, methods and materials for secondary science teaching, high school reading, methods and materials for teaching English, history and philosophy of education, and learning disabilities. ORGANIZATION AND PHYSICAL APPEARANCE: The material suggests the application of performance-based teacher criteria to a number of courses at Milligan College. The guide is glued and stitched in a soft binding. OBJECTIVES AND ACTIVITIES: Specific objectives are given for each course. Activities are oriented around specified teacher behaviors. INSTRUCTIONAL MATERIALS: Bibliographies are given with each section. STUDENT ASSESSMENT: Performance-based assessment. (JB)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: OEG-4-72-0025.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Curriculum; Competency Based Teacher Education; Curriculum Guides; Performance Criteria; Teacher Education; Teacher Education Curriculum; Tennessee